Physical Education in the Al Quran Perspective - Akbar Yusuf; Halimah Basri; Andi Miswar (ETDC: Indonesian Journal of Research and Educational Review, 2026)
Physical education plays a crucial role in shaping human beings holistically, yet in formal educational practice it is often narrowly understood as merely physical activity without the integration of Islamic values. This study aims to examine the concept of physical education from the perspective of the Qur'an, its relationship to physical health and the quality of worship, and its contribution to shaping healthy, strong, and noble individuals. This study uses a qualitative approach of the literature study type with the tafsir mawḍū‘ī method. Data were analyzed from Qur'anic verses, classical and contemporary tafsir literature, hadith, and the views of scholars. The research findings show that the Qur'an views the physical (jasad) and spiritual (rūḥ) dimensions as an inseparable whole. The term "quwwah" is redefined to encompass not only muscular strength but also the aspects of capability (qudrah), moral integrity (wara‘), consistency (wuṣūl), and submission (tawakkul). The Qur'anic narrative about the Prophet Moses (peace be upon him) and Thalut emphasizes that the ideal human quality is a combination of physical strength (al-qawiyy) and moral integrity (al-amīn). Quranic-based physical education plays a vital role in shaping individuals capable of optimally fulfilling the role of khalīfah through maintaining health in line with the principles of maqāṣid al-syarī‘ah, particularly hifẓ al-nafs (protecting the soul) for the perfection of worship. Thus, physical education is an integral component in realizing the ideals of insān kāmil.